Missed anti-D immune globulin administration to postpartum patients in 2 health systems: an unrecognized patient safety riskAJOG Global Reports at a Glance - Kerri Brackney, MD; Gabriel Labbad, MD, FACOG; Alyssa Hersh, MD, MPH; Monica Rincon, MD; David Bar-Shain, MD; Ray Babb, MD; Kelly S. Gibson, MD (Elsevier, 2022)
BACKGROUND: Maternal-fetal Rh-alloimmunization is a rare but potentially fatal event, most often caused by maternal exposure to D-antigen-presenting Rh-positive erythrocytes at the time of delivery. Prophylaxis with anti-D immune globulin is highly effective with a low side-effect profile and results in a dramatically decreased risk of alloimmunization. Postpartum anti-D immune globulin prophylaxis is recommended by national societies to reduce Rh-alloimmunization. We hypothesized that a small number of postpartum patients do not receive prophylaxis as indicated.   OBJECTIVE: We investigated patients in 2 separate health systems that did not receive indicated prophylaxis and devised a suite of Electronic Health Record interventions to prevent future errors. STUDY DESIGN: We reviewed charts retrospectively from Electronic Health Record data of 2 urban academic health systems, the MetroHealth System and Oregon Health & Science University. We identified all Rh-negative postpartum patients and their infants delivering from 2014 to 2019. The primary outcome was the proportion of postpartum patients not receiving indicated anti-D immune globulin prophylaxis. Once cases of missed anti-D immune globulin prophylaxis were identified, we reviewed individual charts to determine the relevant clinical circumstances and potential causes for error. RESULTS: Of 29,801 deliveries over 5 years (15,444 at MetroHealth System and 14,357 at Oregon Health & Science University), there were 3087 Rh-negative postpartum patients, of whom 7 were alloimmunized and ineligible for prophylaxis. Anti-D immune globulin was indicated for 2162 (70.0%) women as they delivered an Rh-positive infant. A total of 37 indicated patients did not receive postpartum anti-D immune globulin. Twenty patients were offered prophylaxis and declined. We missed a total of 17 opportunities, thus our institutions appropriately offered indicated anti-D prophylaxis to 99.2% of patients over a period of 5 years. Of the 17 true misses, anti-D immune globulin was ordered for some patients, whereas others did not have an anti-D immune globulin order placed. A toolkit in the Electronic Health Record consisting of decision-support hard stops, automated documentation, and longitudinal reporting was implemented at the MetroHealth System in the year after its inception. The Toolkit identified and helped prevent 4 potential misses, resulting in a 100% anti-D prophylaxis rate at the MetroHealth System. CONCLUSION: Given the serious nature of Rh-alloimmunization, we believe missed prophylaxis should be a never event. Through examination of our current processes, we identified areas of improvement and developed a Postpartum Anti-D Immune Globulin Prophylaxis Electronic Health Record Toolkit, which showed improvement in administration rates. Such a toolkit has the potential to identify patients appropriately and avoid missed anti-D immune globulin prophylaxis events.